The use of newborn foot length to identify low birth weight and preterm babies in Papua New Guinea: A diagnostic accuracy study. - Alice Mengi; Lisa M Vallely; Moses Laman; Eunice Jally; Janeth Kulimbao; Sharon Warel; Regina Enman; Jimmy Aipit; Nicola Low; Michaela A Riddell (Public Library of Science (PLoS), 2023)
Low birth weight (LBW, <2.50 kg) and preterm birth (PTB, <37 completed weeks of gestation) are important contributors to neonatal death. Newborn foot length has been reported to identify LBW and PTB babies. The objectives of this study were to determine the diagnostic accuracy of foot length to identify LBW and PTB and to compare foot length measurements of a researcher with those of trained volunteers in Papua New Guinea. Newborn babies were enrolled prospectively with written informed consent from their mothers, who were participating in a clinical trial in Madang Province. The reference standards were birth weight, measured by electronic scales and gestational age at birth, based on ultrasound scan and last menstrual period at the first antenatal visit. Newborn foot length was measured within 72 hours of birth with a firm plastic ruler. Optimal foot length cut-off values for LBW and PTB were derived from receiver operating characteristic curve analysis. Bland-Altman analysis was used to assess inter-observer agreement. From 12 October 2019 to 6 January 2021, we enrolled 342 newborns (80% of those eligible); 21.1% (72/342) were LBW and 7.3% (25/342) were PTB. The area under the curve for LBW was 87.0% (95% confidence intervals 82.8-90.2) and for PTB 85.6% (81.5-89.2). The optimal foot length cut-off was <7.7 cm for both LBW (sensitivity 84.7%, 74.7-91.2, specificity 69.6%, 63.9-74.8) and PTB (sensitivity 88.0% (70.0-95.8), specificity 61.8% (56.4-67.0). In 123 babies with paired measurements, the mean difference between the researcher and volunteer measurements was 0.07 cm (95% limits of agreement -0.55 to +0.70) and 7.3% (9/123) of the pairs were outside the 95% limits of agreement. When birth at a health facility is not possible, foot length measurement can identify LBW and PTB in newborns but needs appropriate training for community volunteers and evaluation of its impact on healthcare outcomes.